RANCANG BANGUN APLIKASI MEDIA PEMBELAJARAN SISTEM KOMPUTER BERBASIS MOBILE - Nurva Afitri; Khairi Budayawan (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
Learning media is something that is used to stimulate the mind, attention and appetite of students so that it can encourage the learning process of students. Learning media applications are made based on mobile with the aim to make it easier for students to learn the material and make it easier for students to learn wherever and whenever, especially on computer system lessons. The software used in making this learning media application is Android Studio as a tool and Adobe Photoshop as a design. This learning media application is very helpful for students who miss lessons or forget about old lessons. With the development of current technology, the learning process has begun to shift from a manual process to a more sophisticated process that is using learning media applications. The method in making this application uses the waterfall method. This waterfall method is a sequential design process, often used in software development processes, such as the water process that plunges down through the Conception, Initiation, Analysis, Design, Construction, Testing, Production / Implementation, and maintenance phases. From the problems and methods produced a learning media application to facilitate students in understanding the material. This application is expected to be a learning medium and can be useful for teachers, students and advanced researchers.Keywords: Learning media, Computer Systems, Applications, Android Studio, Waterfall